Differences in Innate Immunologic Response to Group B Streptococcus Between Colonized and Noncolonized Women - Jennifer M. Smith; Rachel H. Respess; David G. Chaffin; Bryan Larsen; Susan H. Jackman (Hindawi Limited, 2001)
Objective: To evaluate the functional capacity of granulocytes and monocytes from pregnant and nonpregnant women in relation to group B streptococcus (GBS) colonization status.